Produtividade e nutrição do tomateiro com fontes alternativas de nutrientes - Simone Nassau Zuba (2007)
With the aim of evaluating alternative sources of nutrients in productivity, nutrition and quality of the fruit of Lycopersicons esculentum (Mill.) cv Santa Clara in agro ecological system, at natural conditions in Montes Claros, Minas Gerais, Brazil. The experimental were started with an experimental design of completely randomized blocks with seven treatments and four repetitions, using eight plants per experimentalplot. The treatments were: (1) conventional fertilization with NPK; (2) organic composition + natural phosphate + rock dust, put one by one; (3) organic composition produced from the addition of natural phosphate and rock dust + green manure fertilization; (4) organic composition produced from the addition of rock dust + natural phosphate + green manure fertilization; (5) organic composition produced from addition of natural phosphate and rock dust + green manure fertilization; (6)natural phosphate + rock dust; and (7) organic composition + natural phosphate + rock dust + green manure fertilization. The largest production was obtained with the use of chemical fertilizers, whereas there was no difference among the treatments with relationship to the content of nutrients foliate. As the class, fruits of medium sizewere the majority, however the treatment prevailed with conventional manure it presented larger percentage of big fruits. The treatments with alternative nutrients show less percentage of serious defect and entomologic defect.